EFFICACY OF LOW-DOSE ASPIRIN IN THE PREVENTION OF HYPERTENSIVE COMPLICATIONS IN PREGNANCY - Silva, Ana Carolina Peixoto da; Veiga, Diego Pacheco Tavares; Neves, Eduarda Santos Elias das; Ribeiro, Mariana Gianisella; Barbosa, Rafaela Gazoli; Cavalcante, Rafaella Storck Gomes (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Objective: To evaluate the efficacy and safety of low-dose aspirin in preventing complications related to hypertension during pregnancy. Methods: This study is a simple literature review. Articles were selected based on searches in the PubMED database using predetermined keywords and inclusion and exclusion criteria. Results: The analyzed articles presented discrepancies regarding the timing of treatment initiation and the recommended optimal dose. In this context, it is possible to conclude that aspirin in higher doses (≥ 100 mg/day), started before the 16th week of gestation, demonstrates efficacy in preventing preeclampsia. Conclusions: This study reinforces the importance of an individualized approach to the pharmacological prevention of hypertensive complications in pregnancy using low-dose aspirin, given the discrepancies found in the analyzed studies regarding dosage, timing of treatment initiation, and its effects.